The Effect of STEM-Based Student Worksheets Assisted by GeoGebra on Conceptual Understanding Ability of Grade X High School Students - Fadya Alfani; Elwan Stiadi; Pratiwi Disha Stanggo (International Journal of Innovation and Education Research, 2025)
The use of teaching materials that were not optimal was one of the causes of students' low ability to understand concepts. The teaching materials used were not fully able to facilitate students' ability to understand concepts, and have not integrated learning approaches or models. Based on these problems, this study aims to determine the effectiveness of STEM-based LKPD assisted by GeoGebra on students' ability to understand mathematical concepts in grade X of senior high school. The research method used in this study was a quantitative approach with a quasi-experimental research design. This study used a quantitative approach with a one-group pretest-posttest experimental design, because it only involves one group without a control group. The data collection technique used was a test of concept comprehension ability in the form of pr-test and post-test. The results showed that the use of GeoGebra-assisted STEM-based LKPD met the effectiveness criteria based on the Paired Sample t-Test and the N-Gain value. The Paired Sample t-Test shows a value of Sig. (2-tailed) of 0.000 < 0.05 so that H₀ was rejected and H₁ was accepted, which means that there was a significant difference between  the pre-test and post-test scores  of students after using the LKPD. In addition, based on the N-Gain value, an average of 0.54 was obtained in the medium category. Based on these results, it could be concluded that STEM-based LKPD assisted by GeoGebra was effective in improving students' ability to understand mathematical concepts.